Realidade lacrimosa: diálogos entre o universo do documentário e a imaginação melodramática - Freire, Mariana Baltar (2008)
This dissertation investigates the mechanisms and implications of a dialogical process established between the domains of documentary and the melodramatic imagination, especially in Brazilian s contemporary documentaries. Such dialogue illuminates several central issues in contemporary world surrounding the connections between public and private spheres towards what could be defined as the hypertrophy of private life. My analyses concerns two scenarios where such dialogue is most interesting and critical: Memory and Intimacy. Those domains reaffirm the important role played by a certain emotional engagement conveyed by the presence of the melodramatic imagination as a fundamental way of addressing such contemporary issues in the analyzed documentaries throughout the performance of their characters